Responses to Toni Morrison's oeuvre in Slovenia - Simona Midžić (Acta Neophilologica)
Toni Morrison, the first African American female winner of the Nobel Prize in Literature, is certainly one of the modern artists whose novels have entered the world's modern literary canon. She is one of the most read novelists in the United States, where all of her novels have been bestsellers. However, only Song of Solomon and Beloved have so far been translated into Slovene. There have been several articles or essays written on Toni Morrison but most of them are simply translations of English articles; the only exception is a study by Jerneja Petrič. This paper presents the Slovene translation of Song ofSolomon by Jože Stabej and the articles written on Toni Morrison by Slovene critics. Jože Stabej is so far the only Slovene translator who has translated Toni Morrison. The author of this article uses some Slovene translations from the novel in comparison to the original to show the main differences appearing because of different grammatical structures of both languages and differences in the two cultures. The articles by Slovene critics are primarily resumes or translations of English originals and have been mainly published in magazines specializing in literature.